An Analytical Study of Chinese Salt (MSG): Is it Halal or Haram - Akbar, Junaid; Khan, Tasnifullah (Journal of Islamic and Religious Studies, 2017)
Monosodium Glutamate is the scientific name of Chinese salt, which also called Ajinomoto. Monosodium Glutamate was first discovered by the Japanese chemist Ikeda Kibunae in 1908. The MSG was firstly derived from seaweed. Later on MSG was got from meat, gluten, and vegetables etc. It can be derived from Najas ul ‘ain and Gher Najas ul ‘ain things. If it was got from Najas ul ‘ain, then there is a question about MSG that is it halal (permissible/ lawful) or haram (non-permissible/unlawful). This research in this article is concluded that if the culture of MSG is halal or the proper Istihalah has been done in Najas; MSG will be halal (permissible/ lawful). However, where no such details are available about the culture of MSG, it should be avoid, although it cannot be declared haram as per Islamic Jurisprudence rules.